Omega-3 fatty acids plus rosuvastatin improves endothelial function in South Asians with dyslipidemia - Catalin Mindrescu (Vascular Health and Risk Management, 2008)
Catalin Mindrescu1,2,3, Rakesh P Gupta1,3, Eileen V Hermance1, Mary C DeVoe1, Vikas R Soma1, John T Coppola1,2, Cezar S Staniloae1,21Comprehensive Cardiovascular Center, Saint Vincent’s Hospital Manhattan, New York, NY, USA; 2New York Medical College, Valhalla, NY, USA; 3Rakesh P Gupta and Catalin Mindrescu contributed equally to this article.Background: The present study was undertaken to investigate the effect of statins plus omega-3 polyunsaturated fatty acids (PUFAs) on endothelial function and lipid profile in South Asians with dyslipidemia and endothelial dysfunction, a population at high risk for premature coronary artery disease.Methods: Thirty subjects were randomized to rosuvastatin 10 mg and omega-3-PUFAs 4 g or rosuvastatin 10 mg. After 4 weeks, omega-3-PUFAs were removed from the first group and added to subjects in the second group. All subjects underwent baseline, 4-, and 8-week assessment of endothelial function and lipid profile.Results: Compared to baseline, omega-3-PUFAs plus rosuvastatin improved endothelial-dependent vasodilation (EDV: −1.42% to 11.36%, p = 0.001), and endothelial-independent vasodilation (EIV: 3.4% to 17.37%, p = 0.002). These effects were lost when omega-3-PUFAs were removed (EDV: 11.36% to 0.59%, p = 0.003). In the second group, rosuvastatin alone failed to improve both EDV and EIV compared to baseline. However, adding omega-3-PUFAs to rosuvastatin, significantly improved EDV (−0.66% to 14.73%, p = 0.001) and EIV (11.02% to 24.5%, p = 0.001). Addition of omega-3-PUFAs further improved the lipid profile (triglycerides 139 to 91 mg/dl, p = 0.006, low-density lipoprotein cholesterol 116 to 88 mg/dl, p = 0.014).Conclusions: Combined therapy with omega-3-PUFAs and rosuvastatin improves endothelial function in South Asian subjects with dyslipidemia and endothelial dysfunction.Keywords: omega-3 fatty acids, endothelial function, South Asians, dyslipidemia, rosuvastatin